A1.31 The type I IFN signature in sorted leukocyte subsets from peripheral blood of rheumatoid arthritis patients; a major contribution by granulocytes. (24th February 2016) - de Jong, TD; Lübbers, J; Turk, S; Vosslamber, S; Mantel, E; Bontkes, HJ; van der Laken, CJ; Bijlsma, JW; van Schaardenburg, D; Verweij, CL
Abstract : Background and objectives: A subgroup of rheumatoid arthritis (RA) patients displays elevated type I IFN response gene (IRG) expression in peripheral blood, which has shown clinical relevance in relation to disease onset and therapy response. Identification of the cell type(s) contributing to this IFN signature could provide insight into its functional consequences and pathologic role in RA. This study aimed to investigate the contribution of the major peripheral leukocyte subsets to the IFN signature in RA. Methods: Blood was collected from 26 early RA patients and lysed directly or separated into mononuclear cells (PBMCs) and polymorphonuclear granulocytes (PMNs). Using flow cytometry, PBMCs were sorted into CD4 + T cells, CD8 + T cells, CD19 + B cells and CD14 + monocytes. mRNA expression levels of three IRGs (RSAD2, IFI44L and MX1), as well as type I IFN receptors IFNAR1 and IFNAR2, were determined in blood and cell subsets by qPCR. IRG expression was averaged to calculate an IFN score for each sample. Results: Patients were designated "IFN high " (n = 8) and "IFN low " (n = 18) based on the IFN score cutoff in peripheral blood from healthy controls. As expected, IFN scores were significantly higher in all cell subsets from IFN high patients compared to IFN low patients. This difference was remarkably large for the PMN fraction (mean 25-fold, p < 0.0001) compared to the other subsets (mean 6–9-fold, p ≤ 0.0009). Moreover, the relative contribution of the PMN fraction was significantly higher than expected from its relative abundance in blood alone (3-fold, p = 0.008), whereas this was 3–7-fold lower for the other subsets (p ≤ 0.063). Both IFNAR1 and IFNAR2 expression was highest in the PMN fraction compared to the other subsets, suggesting increased sensitivity of PMNs to type I IFNs. Concordantly, we observed IFNAR1 and IFNAR2 upregulation compared to healthy controls selectively in RA PMNs (p ≤ 0.0077) but not in the PBMCs. Conclusions: PMNs are the main contributors to the whole blood type I IFN signature in RA patients, which seems due to increased sensitivity to type I IFN signalling. Considering the well-established role of neutrophils in the pathology of RA, this further supports a pathologic role of type I IFN activity in the disease.